Structure and function analyses of the Mmd2 gene in pacific white shrimp Litopenaeus vannamei - Si, Shuqing; Zhang, Xiaojun; Yu, Yang; Zhang, Xiaoxi; Zhong, Xiaoyun; Yuan, Jianbo; Yang, Song; Li, Fuhua (Frontiers in Genetics, 2023)
Monocyte to macrophage differentiation factor 2 (MMD2) gene encodes a member of the progestin and adipoQ receptor (PAQR) family, and plays a key role in growth and development. Our previous studies had found LvMMD2 is a new candidate gene for growth traits in the Pacific white shrimp (Litopenaeus vannamei). In order to understand the underlying mechanism of LvMMD2 affecting the growth of shrimp, we analyzed the gene structure, phylogeny, expression profiles and RNA interference of this gene in L. vannamei. We found the LvMMD2 gene sequence was highly conserved in transmembrane regions, it was widely expressed in different tissues, with the highest expression level in the eye stalk. Knockdown LvMMD2 gene could significantly promote body length and body weight gain, suggesting it is a growth suppressor. Through transcriptome analysis we identified 422 differentially expressed genes (DEGs) between the dsMMD2 group and control group, among which 337 genes were up-regulated in the dsMMD2 group, including numerous muscle-related genes and protein synthesis genes. Further bioinformatics analysis showed that growth, metabolism, and immune-related signal pathway had changed significantly. These results improve our understanding of the conservative structure and function of LvMMD2 gene and show potential applications for the genetics and breeding of shrimp.